Friday Prayer for Women and Right to Worship - Sidiqah, Meliyani (Jurnal Ius Constituendum, 2024)
The purpose is to discover the essence of Friday Prayer for women and provide several views regarding the right to worship for women. The background of this paper is based on the differences of views regarding Friday Prayer for women. These differences lead society to divisions that must be immediately prevented because possible to trigger various actions contrary to the law from certain groups who do not understand the essence of the problem. This paper is normative juridical research using an interdisciplinary approach. Field research is only a complement to support research results. The novelty of this paper presents different research on the substance of Friday Prayer considered essential but received less attention from the public and most researchers, namely Friday Prayer “for women”. The results show that the essence of Friday Prayer for women is sunnah (permitted/not prohibited), based on Surah Al-Jumu’ah verse 9 and hadiths that exclude the obligation of Friday Prayer for women. Besides that, the action that is committed by women to perform Friday Prayer is guaranteed by law. If someone prohibits or forces women to perform or not to perform Friday Prayer, that person has violated someone’s right and the law.